Jewish families in Europe, 1939-Present : history, representation, and memory - Michlic, Joanna Beata HerausgeberIn (HBI Series on Jewish Women, 2017)
Despite many decades of publishing on the Holocaust, there is still surprisingly little scholarship on women, children, and the family. This book fills that gap by offering diverse essays on how WWII, the Holocaust, and the aftermath affected Jewish families and Jewish communities, with an especially close look at the roles played by women, youth, and children. Themes explored include how Jewish parents handled the Nazi threat; rescue and resistance within the Jewish family unit; the transformation of gender roles under duress; youth’s wartime and early postwar experiences; postwar reconstruction of the Jewish family; rehabilitation of Jewish children and youth; and the role of Zionism in shaping the present and future of young survivors. Relying on newly available archival material and novel research in the areas of families, youth, rescue, resistance, gender and memory, the volume is an indispensable guide to current work on the familial and social history of the Holocaust